Clinical value of pre-operative scoring systems to predict leiomyosarcoma: results of a validation study in 177 patients from the NOGGO-REGSA Registry. Issue 5 (14th March 2022) - Condic, Mateja; Egger, Eva Katharina; Hohenberger, Peter; Staerk, Christian; Mayr, Andreas; Armbrust, Robert; Roser, Eva; Mustea, Alexander; Sehouli, Jalid
Abstract : Objectives: Benign leiomyomas are the most common uterine tumors. In contrast, uterine leiomyosarcomas are malignancies with a poor prognosis due to difficulties in early diagnosis and inappropriate surgical treatment. Most often they are diagnosed incidentally after surgery performed for treatment of leiomyoma. As the appropriate surgical treatment is crucial for survival of the patient, there is a high demand to predict leiomyosarcoma pre-operatively. Available scoring systems to discriminate leiomyoma from leiomyosarcoma are based on retrospective studies with limited numbers of patients and are not implemented in routine clinical practice. Methods: The aim of our study was to evaluate a recently published score—the pre-operative leiomyosarcoma (pLMS) score—to determine whether it would have been predictive of leiomyosarcoma in 177 patients from the NOGGO-REGSA study, a German register of histologically proven gynecological sarcoma detected during routine clinical investigation. Results: The threshold of the pLMS score for 'leiomyosarcoma not probable' (< −3) failed for 7.5% of the patients and the threshold 'indicator for leiomyosarcoma' (>+1) was true for 39.1% of the patients. 53.4% of the patients were attributed to the group 'additional investigations are recommended' (−3 to +1). The most relevant parameters in our analysis were suspicious sonography and rapid growth, but neither have been quantitatively defined. Conclusion: In our validation cohort, the pLMS score seems not to be a reliable tool to predict leiomyosarcoma and therefore we do not recommend its clinical implementation to identify leiomyosarcoma.